PENGARUH PEMBERIAN EKSTRAK KULIT BAGIAN DALAM SEMANGKA (Citrullus lanatus) TERHADAP KEUTUHAN MEMBRAN PLASMA DAN ABNORMALITAS MORFOLOGI TIKUS JANTAN (Rattus norvegicus) SETELAH DIPAPAR SUHU PANAS - Reisinta, Dinda; Paramita L, Widya; Hernawati, Tatik; Meles, Dewa Ketut; Madyawati, Sri Pantja; Suprayogi, Tri Wahyu (Ovozoa: Journal of Animal Reproduction, 2018)
This study aims to determined the effect of watermelon's inner rind extract (Citrullus lanatus) towards the integrity of the plasma membrane and morphological abnormalities of male Norway rats's spermatozoa (Rattus norvegicus) after being exposed to hot temperature. The content of lycopene in the inner rind of watermelon serves an antioxidant counteracting free radicals. A total of 20 male Norway rats (Rattus norvegicus) were used in this study with an average age of 2 months. The study was divided into five treatments and four replications, consisting of: K(-) as negative control given CMC Na 0.5% as much as 0.5 ml, P0 as positive control was exposed to 40° C for 1 hour and CMC Na 0.5% of 0.5 ml. P1, P2 and P3 are exposed to 40° C for 1 hour and inner rind extracts of  watermelon with a multilevel dose of P1: 20mg/head/day, P2: 40mg/head/day, and P3: 80mg/head/day that each dose was dissolved in CMC Na 0.5% of 0.5 ml. The results showed that giving inner rind extract of  watermelon to the rats increased the integrity of the plasma membrane and decreased morphological abnormalities of male rat's spermatozoa (Rattus norvegicus). The result of increased the integrity of the plasma membrane and highest decreased morphological abnormality was shown by P3 group given a dose of 80 mg/head/day.